2009
DOI: 10.1038/onc.2009.320
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit mutants require hypoxia-inducible factor 1α to transform melanocytes

Abstract: Many studies have highlighted the critical role of c-Kit in normal melanocyte development but its role in melanoma development remains unclear. Although c-Kit expression is often lost during melanoma progression, a subset of melanoma has been found to overexpress c-Kit and mutations activating c-Kit have recently been identified in some acral and mucosal melanoma. To address the role of these c-Kit mutants in the transformation of melanocytes, we characterized the physiological responses of melanocytes express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 24 publications
(27 reference statements)
4
53
0
1
Order By: Relevance
“…Of 12 tumors with KIT mutations, 5 (42%) were positive for p-ERK and 8 (67%) showed positivity for p-AKT. Similar results have been observed in KIT-mutated GISTs (36) and a KIT-mutated acral melanoma (37). Importantly, treatment of KIT-mutant mucosal melanoma cells in vitro with imatinib results in decreased levels of ERK and AKT phosphorylation (32).…”
Section: Discussionsupporting
confidence: 71%
“…Of 12 tumors with KIT mutations, 5 (42%) were positive for p-ERK and 8 (67%) showed positivity for p-AKT. Similar results have been observed in KIT-mutated GISTs (36) and a KIT-mutated acral melanoma (37). Importantly, treatment of KIT-mutant mucosal melanoma cells in vitro with imatinib results in decreased levels of ERK and AKT phosphorylation (32).…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, many previous publications have utilized the soft agar assay to demonstrate the transformation capacity of oncogenes (Rasmussen et al, 2001;Lu et al, 2008;Syed et al, 2008;Monsel et al, 2010), as this assay is well documented to be predictive of in vivo tumorigenicity (Rhim, 1983;Trainer et al, 1988), malignant potential (Montesano et al, 1977) and drug response (Zirvi et al, 1983;Scholz et al, 1990). Taken together, these observations increase confidence in the oncogenic potential of the miR-506-514 cluster.…”
mentioning
confidence: 92%
“…KIT is expressed at maximum level at the invading edge of tumors, this suggesting a role for dynamic RTK activation in metastasis (Handolias et al, 2010). Monsel et al (Monsel et al, 2010) demonstrated that c-Kit mutated melanocytes require a specific epigenetic environment to be transformed in melanoma cells. c-Kit mutants cause in fact a strong activation of the phosphatidyl-inositol-3 kinase (PI3K) pathway, which, per se, is not sufficient to promote transformation of melanocytes.…”
Section: Ckitmentioning
confidence: 99%
“…A critical role for c-Kit for normal neural crest and normal www.intechopen.com Genetic, Epigenetic and Molecular Changes in Melanoma: A New Paradigm for Biological Classification 41 melanocyte development, (Rother &Jones, 2009) differentiation, proliferation, survival andmigration (Wehrle-Haller, 2003) has been recognized, but its function in melanoma remains somewhat unclear. As a rule, c-Kit expression is lost during melanoma progression, but a subset of melanomas has been found to overexpress it and mutations activating c-Kit, mostly constituted by L576P (up to 50% of mutations), have recently been identified in some mucosal and AL melanoma subtypes (5-20% of cases), but not in cases arising from chronic sun-damaged skin (Rother & Jones, 2009;Monsel et al, 2010). KIT is expressed at maximum level at the invading edge of tumors, this suggesting a role for dynamic RTK activation in metastasis (Handolias et al, 2010).…”
Section: Ckitmentioning
confidence: 99%
See 1 more Smart Citation